PERLINDUNGAN HUKUM TERHADAP HAK-HAK PEKERJA OUTSOURCING BERDASARKAN ASAS KEADILAN - Suyanto, Heru; Nugroho, Andriyanto Adhi (Jurnal Yuridis, 2016)
Outsourcing is delegation of daily management and operations of a business process to outside parties (a provider of outsourcing services). Through delegation, then the management is no longer done by the company, but rather delegated to companies outsourcing services. Protection of workers was intended to guarantee the fundamental rights of workers and guaranteeing equality of opportunity and treatment without any discrimination on the well-being of workers and for the realization of his family by remaining attentive to the developmental progress of the business world and the interests of employers. Laws and regulations related to the protection for workers, namely law No. 13 of 2003 on labor and the implementing regulations of the legislation in the field of employment.